A review on the life and works of the first Filipino Jose Rizal - Delos Santos, Andres R.; Ramos, Orlando H.; Umali, Vanessa D.; Ambida, Melvin N. (Jimczyville Publications, 2014)
"In June 12, 1956, the passing of Republic Act No. 1425 or otherwise known as Rizal Law gave way to the institutionalization of Rizal Course in the tertiary level. It is an imperative requirement for the candidates of both degree and non-degree courses. On this note, this book entitled "Jose Rizal